A retrospective study to analyse the rate of caesarean section according to Robson's 10 group classification in a peripheral hospital in a metropolitan city - Kore, Siddhi S.; Shams, Fatema; Chilkund, Jayanth; Kore, Gauri (International Journal of Research in Medical Sciences, 2021)
Background: In the past several decades, a pattern of rapid increases in Caesarean section (CS) delivery rates has been observed worldwide, as also in India. It is important to identify the reason behind the rising rates of CS since they can pose unnecessary risks to the mother and the neonate. The aim of the study was to analyse the CS rate in the ten groups as per Robson’s ten group classification, in a peripheral hospital in a metropolitan city. By this study we have tried to identify specific groups of women to be targeted to reduce CS rates. Methods: This is a retrospective study carried out at a peripheral hospital in Mumbai, India. It included all women who had delivered in the hospital from January, 2019 to December, 2019. The sample size was 2603. Results: Under this study, we found out that the rate of CS delivery is higher than what is recommended by WHO in Robson’s group 2, 5 and 6. Conclusions: This study will help us carry out targeted interventions so as to reduce the CS rates in these groups.